Neural Networks in Early Fear Bias Development : A Study of Infants - Audah, Hilyatushalihah Kholis (My University, 2023)
The development of emotion perception starts very early on during infancy. Especially, in processes relevant for social settings, with facial expressions as the dominant stimuli used in research. An attentional bias to fearful faces emerges at around 5-7 months old and is linked with amygdala volumes. The underlying structural pathways are still unclear and is relevant to understanding healthy emotional development. This study attempts to delineate the white matter (WM) tracts involved in fear emotion processing using data collected in the FinnBrain Birth Cohort study. The main measures are diffusion magnetic resonance images of neonatal brains and behavioural measures using eye tracking with an overlap paradigm to obtain fear bias scores. The study expects there to be a positive relationship between tract integrity of the inferior longitudinal fasciculus, uncinate fasciculus and cingulum with fear bias scores. Results indicate a face and fear bias is present at 8-months old. However, none of the WM tracts can predict fear bias scores. This may be due to the developmental timing related to neonatal brain maturation and the emergence of an attentional bias to fear in infants. These reasons and alternative explanations are discussed.
Keywords: fear bias, white matter tracts, DTI, eye tracking, emotion perception, emotional development